PEMANFAATAN MEDIA DIGITAL SEBAGAI WUJUD PEMBERDAYAAN MASYARAKAT KABUPATEN TAKALAR; PENERAPAN LITERASI DIGITAL - Sujariati, Sujariati; Wanci, Risman; Qalbi, Nur (FKIP UKI TORAJA, 2023)
This training has done in Lengkese district of Takalar regency Sulawesi-selatan. This training goals to educate the society in using technology be a tools of trading activity and trading incomes. The training also aims to introduce the society, citizen in the village of Lengkese district about how to function the technology in maintain their need of live. This training has done around a day by some lecturers from Adpertisi institute of Makassar. And the result achievement was good responses and practice actively by the participant in applying the materials and practicing the mobile phone directly for trading communication. The result showed as positive responses from the participant because they give feedback to the presenter with some questions dealt with how to use and operate the fixture and application on digital media in well.